Influência do uso de probióticos comerciais sobre a comunidade fitoplanctônica em cultivo intensivo do camarão marinho Litopenaeus vannamei - Ferreira, André Luis de Sousa (Universidade Federal Rural do Semi-Árido, 2021)
Currently, with the intensification of shrimp farming, there is a greater demand for the use of fertilizers and probiotics, as modulators of the cultivation ecosystem. This work aimed to study the effects of different commercial microbial agents on the p hytoplankton community in an intensive cultivation of marine shrimp (Litopenaeus vannamei). More specifically, characterize the phytoplankton community; qualitatively and quantitatively verify changes in the structure of the community; determine the relative abundance, frequency of occurrence and diversity; to correlate the observed variations in phytoplankton composition and proportion with shrimp survival and to investigate the potential role of probiotics in crop management water. The experiment was carried out in 21 tanks. About 150 shrimp were added to each tank at a rate of 150 shrimp per m². The experimental design was completely randomized with 7 treatments and 3 replications. Treatments P1, P2, P3, P4 were related to commercial probiotics (Bacillus sp., Lactobacillus sp. Saccharomyces cerevisiae and Pediococcus), P5 and P6 were related to autochthonous probiotic consortia (Bacillus sp. and Coccus sp) and in the last one, treatment control, no probiotics were used. Seven days before population, the units were fertilized. Probiotics were added twice a week. Every five days, the same concentration was added, until the conclusion of the experimental phase. To obtain the growth curve, the performance of the animals was evaluated and, at the end of the cultivation, the parameters for evaluating the zootechnical performance were evaluated. The environmental parameters were monitored and weekly collections were carried out to characterize the phytoplankton community, with water being collected in vertical samples for the quantitative and qualitative determination of the phytoplankton. Relative abundance (AR) and frequency of occurrence (FO) were verified. The results showed a composition of the phytoplankton community distributed in five taxonomic classes: Bacillariophyceae, Chlorophyceae, Cyanobacteria, Dinophyceae and Euglenophyceae. The most representative class was Bacillariophyceae with an occurrence percentage corresponding to (43.6%), followed by the other classes: Chlorophyceous, with an occurrence percentage equal to (26.1%), Cyanophyceous, with an occurrence percentage of (18.1%), Dinoflagellates with an occurrence percentage of (8.1%) and Euglenaceas, whose occurrence percentage was (4.1%). There were no dominant groups and the most representative group was the Class Bacillariophyceae classified as abundant, with percentage (> 40% ≤ 70%) and the Class Chlorophyceae classified as not very abundant, with percentage (40% - 10%). The representatives of the other Classes were classified as rare with percentage of abundance (< 10%). As for the frequency of occurrence by classes, the classes Bacillariophyceae, Chlorophyceae and Cyanobacteria were considered very frequent (> 70%). Class Dinophycea was registered as frequent, with percentage of frequency (between 40% and 70%) and Class Euglenaceae was considered as infrequent, with percentage of frequency (between 10% and 40%). There was no group classified as sporadic. The relative density registered for the Classes that made up the Phytoplankton Community was relatively distinct. However, the percentage of relative density followed a similar pattern, except in Treatment P2, in which there was a higher percentage of Classes Euglenaceae and Chloroficeae and in the Control Group with a higher percentage of density related to Class Cyanobacteria. Regarding the application of probiotics, the results were not clear enough in relation to the action of different probiotics on the composition of the Phytoplankton Community and on the correlations between the composition and phytoplankton proportion with shrimp survival. It is likely that there was an unsuccessful colonization of probiotics, due to the concentration of probiotics applied and the short production period of the marine shrimp, L. vannamei.
Keywords: Aquicultura; Organismos planctônicos; Produtos bacterianos comerciais; Carcinicultura; Sustentabilidade; CIENCIAS AGRARIAS::RECURSOS PESQUEIROS E ENGENHARIA DE PESCA